QUEM FINANCIA A BAIXARIA É CONTRA A CIDADANIA : Análise Da Campanha Pela Qualidade Da Televisão (2002 A 2006) - Carvalho, Marcelle de Almeida (2007)
This thesis describes and analyzes the Campaign Who Finances Baixaria is Against the Citizenship , in the period of 2002 the 2006. The research examines the strategies of the Campaign that has for objective the valuation of the human rights and the dignity of the citizen in the television programs. It observes its form of organization, social mobilization and influence in the improvement of the quality of the televising programming. It argues the paper of the State and the limits of the fiscalization. It investigates, still, the repercussion of the Campaign in the actions of being able constituted them: Executive, Legislative and Judiciary. One is about a Study of Case of qualitative nature. The strategies of communication and the actions of the Campaign mobilized the civil society, the media and the Public Department in favor of the quality of the programming. Sponsors were convinced to will not associate his marks to programs of doubtful quality. Senders of open television were punished and to even obliged it replace quality decrease programs by independent programs selected by the Collective Intervozes. In five years of action, the Campaign generated barely 30 thousand denunciations against the sordidness in the TV and provoked the change of the Indicative Classification for programs of television with the edition of the Entrance 264/07 of the Department of the Justice, published in the day 12 of February of 2007. To new Entrance establishes stricter rules for the sector, with criteria already adopted in others countries and comes provoking reactions of the businessmen of television. Finally, to research showed the difficulty of dialogue between the different sectors of the civil society with the businessmen of television and the Department of the Communications. It reveals, still, that the social control of the open TV is necessary for guarantee the quality of the programming in the television and that the social mobilization, when organized, produces results in aid of the public interest.(AU)